Implementation of cooperative learning model teams games tournament to improve student science learning outcome of junior high school - Bella Novritasari; Beni Setiawan; Muhamad Arif Mahdiannur (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This study aims to describe the improvement in science learning outcomes for junior high schools on the Digestive System material with the Teams Games Tournament TGT. The study was carried out at junior high school SMPN 28 Surabaya, Indonesia. Pre-experimental designs were used in the study. This study was aimed at 33 students in grade eight. Data were collected by observation, written test, and response questionnaire. This study obtained the average learning implementation with a very good percentage (93%). It can be concluded that the average N-gain is high. Student responses during learning also gave a positive response. The student response questionnaire shows a high percentage (89.14%), which means that they agree with the implementation of learning using this model. In conclusion, the TGT in the learning process can improve student learning outcomes, especially in the material of the human digestive system.